The Limitations of Living Law in Indonesian Criminal Law Reform: An Effort to Realize Justice - Febrianty, Yenny; Ishwara, Ade Sathya Sanathana; Priambada, Bintara Sura; Hulwanullah, Hikam (Magister of Law, Faculty of Law, University of Mataram, 2023)
One of the important points of criminal law reform in the Criminal Code is the regulatory provision regarding living law. The Criminal Code authentically determines that living law is customary criminal law, which is declared valid and further regulated through Local Regulations. The absence of limitations related to customary criminal law standards that can be qualified as a living law has the potential to cause injustice. This study aims to analyze the urgency and the formulation of limitations on living law arrangements in the Criminal Code in realizing justice. The results of the study show that the urgency regarding limitations on living law arrangements in the Criminal Code is meant to protect human rights while at the same time preventing potential criminalization. The formulation of limitations of the living law arrangements in the Criminal Code is to realize justice. Therefore, the limitations of customary criminal law can be categorized as a living law according to the Criminal Code, that are: indigenous people still practice the law; these customary crimes do not conflict with the principles of the rule of law; they do not conflict with Pancasila values; and the crimes are further formulated by local regulations.